1980
DOI: 10.1111/j.1467-8489.1980.tb00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Supply Response in the Australian Sheep Industry: A Case for Disaggregation and Dynamics*

Abstract: A.Microeconomic capital goods theory was utilised to provide a theoretical framework on which a dynamic econometric model was based. Econometric procedures were then employed in an analysis of sheep producers' decision making regarding the annual supplies of wool, lamb and mutton, and annual changes in the inventory levels of sheep, lambs and ewes maintained for breeding purposes.Estimates show that wool prices provide the long-run stimulus for increases and decreases in the sheep flock while mutton and lamb p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
3
1
0
Order By: Relevance
“…The unimportance of the wheat price variable in the alternate product equations suggested that movements in wheat prices do not directly affect livestock production enterprises. A similar conclusion was reached by Reynolds and Gardiner (1980) in their supply study of the Australian sheep industry. They argue that, because of the practice of ley rotation on mixed farms, producers tend to make separate production choices within livestock enterprise combinations and also separate choices within cropping alternatives.…”
Section: Discussionsupporting
confidence: 80%
“…The unimportance of the wheat price variable in the alternate product equations suggested that movements in wheat prices do not directly affect livestock production enterprises. A similar conclusion was reached by Reynolds and Gardiner (1980) in their supply study of the Australian sheep industry. They argue that, because of the practice of ley rotation on mixed farms, producers tend to make separate production choices within livestock enterprise combinations and also separate choices within cropping alternatives.…”
Section: Discussionsupporting
confidence: 80%
“…Those options incorporating both disaggregated and adjusted data were able to adjust more quickly to a shock because breeding decisions were more responsive to price changes (particuiarly in the longer term) and were less predetermined by previous breeding decisions. This study has confirmed the prognosis of Reynolds and Gardiner (1980), who called for greater disaggregation in livestock inventory modelling, and has taken the disaggregation procedures further.…”
Section: Discussionsupporting
confidence: 72%
“…In option (ii), separate inventories are specified for the mating intentions to short wool, long wool and Corriedale-Polwarth rams to capture the composition and distribution of the Australian lamb breeding inventory, after the observation that the producers of these breeds respond differently to changes in pastoral conditions and the returns to competitive enterprises (Reynolds and Gardiner 1980). Here, the aggregate breeding inventory is decomposed into three equations to explain matings to the three major British breed categories to produce the aggregate inventory (INEWAU).…”
Section: Option (Ii): Disaggregated British Breed Inventoriesmentioning
confidence: 99%
“…Other variables unsuccessfully tried in the supply equation included: the clean yield and the real expected price of wheat as another substitution possibility. The relative importance of expected beef prices compared to expected wheat prices is consistent with results from other studies, seeReynolds and Gardiner (1980).…”
supporting
confidence: 90%